A study on key determinants of economic growth in Malaysia: foreign direct investment, inflation rate, interest rate, trade openness and unemployment / Fatin Nabila Shaharuddin - Shaharuddin, Fatin Nabila (Faculty of Business and Management, 2018)
Economic growth in Malaysia has always been inconsistent over the time and it is affected due to factors that influence its growth rate. This study is conducted to determine the relationship between independent variables such as foreign direct investment, inflation rate, interest rate, trade openness and unemployment towards economic growth in Malaysia. The annual time series data were obtained from Thomson Reuters DataStream and this study covers the period between 1987 until 2017. The tools applied to estimate the relationship between dependent variable and independent variables is Linear Regression Model. Overall findings based on Multiple Linear regression, the result concludes that foreign direct investment, inflation rate and interest rate has statistically significant impact towards economic growth in Malaysia with positive correlation except for inflation rate with negative relationship. However, trade openness and unemployment were found to be insignificantly impactful with positive correlation. Theoretically, interest rate and unemployment would bring negative impact towards economic growth, but this paper provides different results where both independent variable has positive relationship with economic growth. Based on the results, recommendations are made for policymakers and economist to help them in mapping out suitable policies that will sustain economic growth for the long run.